Structure, Expression, and Functional Analysis of the Hexokinase Gene Family in Cassava - Geng, Meng-Ting (Int J Mol Sci, 2017)
Hexokinase (HXK) proteins play important roles in catalyzing hexose phosphorylation and sugar sensing and signaling. To investigate the roles of HXKs in cassava tuber root development, seven HXK genes (MeHXK1–7) were isolated and analyzed. A phylogenetic analysis revealed that the MeHXK family can be divided into five subfamilies of plant HXKs. MeHXKs were clearly divided into type A (MeHXK1) and type B (MeHXK2–7) based on their N-terminal sequences. MeHXK1–5 all had typical conserved regions and similar protein structures to the HXKs of other plants; while MeHXK6–7 lacked some of the conserved regions. An expression analysis of the MeHXK genes in cassava organs or tissues demonstrated that MeHXK2 is the dominant HXK in all the examined tissues (leaves, stems, fruits, tuber phloems, and tuber xylems). Notably, the expression of MeHXK2 and the enzymatic activity of HXK were higher at the initial and expanding tuber stages, and lower at the mature tuber stage. Furthermore, the HXK activity of MeHXK2 was identified by functional complementation of the HXK-deficient yeast strain YSH7.4-3C (hxk1, hxk2, glk1). The gene expression and enzymatic activity of MeHXK2 suggest that it might be the main enzyme for hexose phosphorylation during cassava tuber root development, which is involved in sucrose metabolism to regulate the accumulation of starch.